Paederia scandens extract alleviates obesity via modulating the gut microbiota and serum metabolome disorder - Yang, Yuanyuan; Si, Jinglei; Mo, Jiayuan; Li, Jin; Pan, Bin; Pan, Yi; Jiang, Lihe; Wang, Decai; Feng, Xueping (Frontiers in Microbiology, 2025)
Obesity is increasingly becoming a challenge with China’s economic development. There is an urgent need to identify more affordable methods to combat this condition. Paederia scandens (PS), a cost-effective herbal remedy widely used in China for treating inflammation and pain, shows potential in this regard. To investigate its anti-obesity mechanisms, we established a high-fat diet (HFD)-induced obesity model in mice. The obese mice subsequently received daily oral gavage of PS extract for 21 consecutive days. Upon the completion of the experiment, blood samples were collected to analyze lipid profiles, including total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL-C), and low-density lipoprotein (LDL-C). Abdominal adipose tissue was subjected to hematoxylin–eosin (HE) staining for histological analysis, while fecal samples underwent 16S rRNA sequencing to assess gut microbiota composition. Our findings revealed that PS supplementation significantly reduced body weight, lipid metabolism biomarkers, and adipocyte size. PS treatment also restored gut microbial diversity, with 19 specific microbial taxa and 25 KEGG pathways identified as potential mediators of its anti-obesity effects. Notably, PS modulated key obesity-associated gut microbiota, including Alistipes, Lachnoclostridium, Odoribacter, Prevotellaceae UCG-001, Rikenellaceae RC9-gut group, and norank_g Bacteroidales S24-7 group. Serum metabolomics analysis implicated L-ascorbic acid, stevioside, allopurinol, and gingerol, along with amino acid and energy metabolism pathways, in the anti-obesity mechanism of PS. These results provide novel theoretical insights into the therapeutic potential of PS for obesity prevention and treatment.